A macrocyclic [60]fullerene-porphyrin dyad involving φ-φ stacking interactions - Dietel, Elke; Hirsch, Andreas; Eichhorn, Emerich; Rieker, Anton; Hackbarth, St.; Röder, Beate (Chemical Communications, 1998)
The very regioselective twofold cyclopropanation of C with a porphyrin bismalonate leads to a C symmetrical [60]fullerene-porphyrin dyad with pronounced electronic interactions between the two π-π stacked chromophores.